Asthma, bones and corticosteroids: Are inhaled corticosteroids associated with fractures in children with asthma?. (1st June 2017) - Zieck, Saskia E; George, Johnson; Blakeley, Brooke A; Welsh, Liam; James, Simon; Ranganathan, Sarath; Simm, Peter; Lim, Angelina
Abstract : Aim: The prevalence of asthma worldwide among older children varies between 10 and 20%. One of the most effective therapies to treat asthma and prevent exacerbations is inhaled corticosteroids (ICSs). Systemic corticosteroids are known to decrease bone mineral density and increase the risk of fractures among children, but little is known about the effect of ICSs on fracture risk in children with asthma. The aim of this study was to investigate the fracture rates in children with asthma using ICSs. Methods: A survey on fracture history and risk, bone health and asthma was administered by a researcher to children aged 6–18 years attending a tertiary care children's hospital in Melbourne, Australia over a 6‐month period. Fracture risks were compared in children on low or high dose ICS with those not on any ICS and non‐asthmatics. Results: A total of 216 healthy control participants were compared with 211 children with asthma – 22% ( n  = 46) on low dose ICS therapy, 44% ( n  = 94) on high dose ICS and 34% ( n  = 71) not on any ICS. There was no difference in the incidence of fractures between children with asthma (24.6% n  = 53) and healthy controls (24% n  = 51) (χ 2  = 0.132; P  = 0.717). There were no differences in fracture incidence in the sub‐groups of children with asthma ( P  = 0.695). Conclusion: ICS use was not associated with fracture risk in children with asthma.